Analysis of the Impact of the Number of Hotels, the Number of Tourists, and the Number of Tourist Attractions on the Revenue of the Tourism Sector in Wonosobo Regency From 2014 To 2022 - Firdaus Aldi Saputra; Endah Saptutyningsih (Publikasi Indonesia, 2025)
Wonosobo Regency is one of the leading tourist destinations in Central Java with significant natural and cultural potential. However, fluctuations in tourism sector revenues, especially during the COVID-19 pandemic, indicate the need to identify factors that affect the economic performance of the sector. This research aims to analyze the impact of the number of hotels, the number of tourists, and the number of tourist attractions on tourism sector income in Wonosobo Regency from 2014 to 2022. The data in this study were obtained from the Central Statistics Agency of Wonosobo Regency, the Tourism and Culture Office of Wonosobo Regency, and other sources related to this research. This study uses Multiple Linear Regression Analysis with EViews 10 as the analysis tool. Based on the results of the analysis that has been carried out, it was found that the number of tourists and the number of hotels have a positive and significant influence, while the number of tourist attractions has a negative and significant influence. The R² result obtained was 0.880161, showing that the variables under study (number of tourists, number of hotels, and number of tourist attractions) influence tourism sector income by 88%, while other variables outside the study account for the remaining 12%. These findings underscore the need to prioritize quality over quantity in tourism development. Local governments should enhance existing attractions, boost promotion, and streamline hotel investment processes. Tourism stakeholders must innovate services and collaborate to strengthen sustainable appeal.